Important of Maternal and child health care and role of nurses about it - Mehri F (Iran University of Medical Sciences, 1989)
It is best to be considered father, mother and children health instead of mother and children health, because of health of children is related to father and mother health. Also The health of children should be considered before birth and even before the boys and girls get married.  So youth should be received necessary education for becoming a father, mother and nurturing healthy children. Implementation of such training is part of responsibility of health community workers. They should prepare current generation for creation better and healthy generation. Perhaps this was one of the goals of Alma Ata conference, which were organized in by 1357 by UNICEF and the world health organization.